Mapping of Bancroftian Filariasis in Cameroon: Prospects for Elimination. - Hugues C Nana-Djeunga; Jules B Tchatchueng-Mbougua; Jean Bopda; Steve Mbickmen-Tchana; Nathalie Elong-Kana; Etienne Nnomzo'o; Julie Akame; Ann Tarini; Yaobi Zhang; Flobert Njiokou; Joseph Kamgno (Public Library of Science (PLoS), 2015)
BACKGROUND:Lymphatic filariasis (LF) is one of the most debilitating neglected tropical diseases (NTDs). It still presents as an important public health problem in many countries in the tropics. In Cameroon, where many NTDs are endemic, only scant data describing the situation regarding LF epidemiology was available. The aim of this study was to describe the current situation regarding LF infection in Cameroon, and to map this infection and accurately delineate areas where mass drug administration (MDA) was required. METHODOLOGY:The endemicity status and distribution of LF was assessed in eight of the ten Regions of Cameroon by a rapid-format card test for detection of W. bancrofti antigen (immunochromatographic test, ICT). The baseline data required to monitor the effectiveness of MDA was collected by assessing microfilariaemia in nocturnal calibrated thick blood smears in sentinel sites selected in the health districts where ICT positivity rate was ≥ 1%. PRINCIPAL FINDINGS:Among the 120 health districts visited in the eight Regions during ICT survey, 106 (88.3%) were found to be endemic for LF (i.e. had ICT positivity rate ≥ 1%), with infection rate from 1.0% (95% CI: 0.2-5.5) to 20.0% (95% CI: 10-30). The overall infection rate during the night blood survey was 0.11% (95% CI: 0.08-0.16) in 11 health districts out of the 106 surveyed; the arithmetic mean for microfilaria density was 1.19 mf/ml (95% CI: 0.13-2.26) for the total population examined. CONCLUSION/SIGNIFICANCE:ICT card test results showed that LF was endemic in all the Regions and in about 90% of the health districts surveyed. All of these health districts qualified for MDA (i.e. ICT positivity rate ≥ 1%). Microfilariaemia data collected as part of this study provided the national program with baseline data (sentinel sites) necessary to measure the impact of MDA on the endemicity level and transmission of LF important for the 2020 deadline for global elimination.